Logic Puzzles as Mental Gymnastics for LSAT Preparation - Karapetyan, Marina (Armenian Folia Anglistika, 2011)
The article highlights the methods that help developing skills to express logical and critical thoughts and to hold attention which are of great importance in exam tests of law school in the USA, Canada, Australia and now in Armenia (LSAT). Solving logic puzzles and games is one of these methods. It gives an opportunity to future lawyers, as well as people with other professions to develop their deductive thinking as well as to improve the necessary skills to categorize, group and match.